2012
DOI: 10.1136/bmjopen-2012-000824
|View full text |Cite
|
Sign up to set email alerts
|

A before and after study on personality assessment in adolescents exposed to the 2009 earthquake in L'Aquila, Italy: influence of sports practice

Abstract: ObjectiveTo assess and estimate the personality changes that occurred before and after the 2009 earthquake in L'Aquila and to model the ways that the earthquake affected adolescents according to gender and sport practice. The consequences of earthquakes on psychological health are long lasting for portions of the population, depending on age, gender, social conditions and individual experiences. Sports activities are considered a factor with which to test the overall earthquake impact on individual and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The destruction wrought by the earthquake resulted in 308 deaths and numerous injuries. The social and psychological impact on the entire community was immense [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The destruction wrought by the earthquake resulted in 308 deaths and numerous injuries. The social and psychological impact on the entire community was immense [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the weeks and months following a natural disaster, as communities begin the long, slow process of rebuilding their lives, recreational sport can play a valuable role in facilitating individual resilience and coping, re-establishing networks, and making new social connections. A select few studies have attempted to measure the effectiveness of sport programs implemented by aid organizations following natural disaster (Kunz, 2009; Valenti et al, 2012). However, this project is among the first to create space for the voices of residents who use recreational, grassroots sporting participation to help make meaning of their lives in post-disaster geographies.…”
mentioning
confidence: 99%
“…The results of analysis of covariance showed that there were significant differences in the scores of Center for Epidemiologic Studies Depression Scale (CES-D) and Six-item Kessler Psychological Distress Scale (K6) ( p = .01, p = .04) among the three groups with age, gender and alcohol drinking habit as covariates, CES-D score was obviously higher among short-time walkers ( p = .004), and walking for 30–60 min every day had the best effect. Another cross-sectional survey of 179 adolescents (14–18 years old) also showed that adolescents who regularly exercised before the earthquake (at least twice a week, no less than 1 h each time) had significant lower levels of anxiety after the earthquake than those who did not regularly exercise (−3.43 ± 0.78, p = .00), in addition, the anxiety score of adolescents who often exercised after the earthquake was 3.43 points lower than that of those who did not exercise (Valenti et al, 2012 ). Tian et al ( 2014 ) studied 4604 Chinese adolescents after the Wenchuan earthquake, and the results of multiple logistic regression analysis showed that high levels of physical exercise (Odds = 0.655, p = .03, 95%CI: 0.479–0.863) and social support (Odds = 0.977, p < .01, 95%CI: 0.965–0.988) were negative risk factors for PTSD of adolescents after the earthquake.…”
Section: Resultsmentioning
confidence: 98%
“… Tokyo earthquake Utsumi et al ( 2020 ) Japan Cross-sectional survey Adults (>20 years old) 718 K6; Center for Epidemiologic Studies Depression Scale (CES-D); the Impact of Event Scale-Revised (IES-R) Walking time was negatively correlated with the depressive symptoms of residents in the post-earthquake area, and walking for 30–60 min every day worked best. L’Aquila earthquake, Italy Valenti et al ( 2012 ) Italy Cross-sectional survey Adolescents (aged 14–18) 179 Minnesota Multiphasic Personality Inventoried Adolescents (MMPI-A) Exercising at least twice a week for no less than 60 min each time could reduce the anxiety level of adolescents in the post-earthquake areas. Tokyo earthquake Nozue et al ( 2017 ) Japan Cross-sectional survey Young, middle-aged and elderly people 6668 K6 Interventions targeting physical activity and dietary intake had positive effects on the physical and mental health of Tokyo earthquake survivors.…”
Section: Methodsmentioning
confidence: 99%